2018
DOI: 10.1016/j.jue.2018.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Substance abuse treatment centers and local crime

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
58
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(66 citation statements)
references
References 50 publications
6
58
2
Order By: Relevance
“…It is important to stress that 24/7 does not require participants to enter treatment or engage in other services; this seems to be largely a deterrent effect, although one mechanism through which that deterrence might work is giving participants a reason to seek treatment on their own, whether paid professional treatment or self-help (e.g., Alcoholics Anonymous). The availability of substance abuse treatment facilities in communities has been found to reduce both drug-induced mortality (Swensen 2015) and both violent and acquisitive crime (Bondurant, Lindo, and Swensen 2018). Without stronger understanding of the mechanism resulting in reduced alcohol consumption and crime through 24/7, we cannot assess the degree to which the program is a cost-effective substitute for substance abuse treatment or specialty courts for some participants.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to stress that 24/7 does not require participants to enter treatment or engage in other services; this seems to be largely a deterrent effect, although one mechanism through which that deterrence might work is giving participants a reason to seek treatment on their own, whether paid professional treatment or self-help (e.g., Alcoholics Anonymous). The availability of substance abuse treatment facilities in communities has been found to reduce both drug-induced mortality (Swensen 2015) and both violent and acquisitive crime (Bondurant, Lindo, and Swensen 2018). Without stronger understanding of the mechanism resulting in reduced alcohol consumption and crime through 24/7, we cannot assess the degree to which the program is a cost-effective substitute for substance abuse treatment or specialty courts for some participants.…”
Section: Discussionmentioning
confidence: 99%
“…For the public insurance variable, which is continuous, how best to test parallel trends is less clear as there is no specific event, rather states increase, and in some cases decrease, income thresholds. We follow recent work by Bondurant, Lindo, and Swensen (2018) and Swensen (2015) and include the policy measured the years before (t-1) and after (t+1) the current period (Appendix Tables 14A to 14B). If we observe that the coefficient estimates on the policy variable measured in the t-1 period are statistically indistinguishable from zero, this pattern of results would provide suggestive evidence that our data satisfy parallel trends.…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…The third reason is that Medicaid increases access to treatment for those suffering from behavioral disorders or drug addiction. A large body of research has shown that substance abuse treatment is effective at reducing crime and recidivism (e.g., Bondurant et al, 2018;Campbell et al, 2007;Deck et al, 2009;Lurigio, 2000;Marsch, 1998;Mitchell et al, 2007;Prendergast et al, 2002), and although the literature on the effect of mental health treatment is less conclusive, it is suggestive of a small or moderate crime reduction (e.g., Cuellar et al, 2004;Evans Cuellar et al, 2006;Frank and McGuire, 2011;Constantine et al, 2012;Martin et al, 2012;Morrissey et al, 2007;Morrissey et al, 2016;Van Dorn et al, 2013). If Medicaid helps newly eligible individuals obtain treatment for mental health issues they would otherwise ignore (or treat less effectively), it could potentially induce a reduction in overall crime rates.…”
Section: Introductionmentioning
confidence: 99%